In-Hospital Newborn Falls and Near Miss Events: A Need to Report - Unal, Sezin; Demirel, Nihal; Tokgoz-Cuni, Betül; İyigün, Fatma; Moraloglu Tekin, Ozlem; Baş, Ahmet Y. (American Journal of Perinatology, 2023)
Objective This study aimed to evaluate the clinical characteristics of the neonates who fell in the maternity ward and identify the incidence of near miss events during the immediate postpartum period.Study Design The study consisted of two steps. The retrospective part included the evaluation of admissions due to the in-hospital newborn fall for 6 years. The prospective part included the assessment of the near miss events (any probability of falling of the newborn; either cosleeping or an incident with a possible consequence of falling of the newborn) in the postpartum clinic (<72 hours after delivery) for a period of 4 weeks. The details of the events and clinical outcomes were recorded. A questionnaire about fatigue was administered to mothers who experienced near miss event.Results Seventeen in-hospital newborn falls were recorded: 1.8 to 2.4/10,000 live births. The median age of the neonates when the fall occurred was 22 (16–34) postnatal hours. Fourteen events (82%) occurred between 10 p.m. and 6 a.m. All neonates who experienced a fall were discharged without any known adverse outcomes. Twelve mothers (71%) had experienced a near miss event before. In the prospective arm of the study, 67 out of 804 mothers (8.3%) were found to experience a near miss event (44/1,000 days of postpartum hospitalization). Thirty-two events (49%) occurred in the first postpartum day. Fifty-two events (78%) occurred between 10 p.m. and 6 a.m. Fifty-eight mothers (86%) had no companion. Sixty-three percent of the mothers expressed intense fatigue after delivery.Conclusion In-hospital newborn fall may occur in the postpartum period, and near miss events should warn clinicians for a probable fall event. The nighttime shift requires more attention regarding the prevention of both the fall and the near miss events. Immediate postpartum mothers are needed to be observed carefully.Key Points
Keywords: newborn fall; hospital; cosleeping